Residência São Jerônimo: entre o acontecimento, a memória e a narrativa - Alexandre Romariz Sequeira (2020)
Based on a collaborative artistic proposition, the present thesis investigates the relations that are established between the event, the memory, the narrative and the poetic self-fictions. From the perspective of the last resident of an old house full of memories and in a process of ongoing disappearance, the study brings together considerations about image, time, ruin and allegory to analyze poetic statements that approximate and confuse the act of creating with the act of living. We are interested in investigating the incessant movement of creative imitation of the lived temporal experience ruled by a logic of forgetting and appropriation of other stories. We pay particular attention to the role of images in this act and its possible implications in relation to our sense of otherness. In this sense, the research follows the transformation of the house into a living space between artists bringing together different poetic statements in order to blur the boundaries between what is personal, what is of the other and what is of humanity. The thesis intends to attest that it is by the extension of time as a distension, and by the rewriting exercise of living that we, at the same time, attain the impressions of the past, the multiplicity of the present and its laceration in signs of the future.